2009
DOI: 10.1089/pho.2008.2354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Response of Human Embryonic Stem Cells and Their Differentiated Progenies to Oxidative Stress

Abstract: Undifferentiated hESC are intrinsically more resistant to oxidative stress compared to their spontaneously differentiated fibroblastic progenies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
(36 reference statements)
2
11
2
Order By: Relevance
“…Hirano and Tamae [12] and Kuboyama et al [13], also reported that undifferentiated embryonic stem cells were more resistant to DNA damage induced by the ROS -8-oxoguanine (which is known to generate GC-to-TA point mutations in genomic DNA), as compared to their differentiated progenies. These findings are thus consistent with the results of this study, as well as our previous studies [5,6].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Hirano and Tamae [12] and Kuboyama et al [13], also reported that undifferentiated embryonic stem cells were more resistant to DNA damage induced by the ROS -8-oxoguanine (which is known to generate GC-to-TA point mutations in genomic DNA), as compared to their differentiated progenies. These findings are thus consistent with the results of this study, as well as our previous studies [5,6].…”
Section: Discussionsupporting
confidence: 94%
“…The results conclusively demonstrated that hESC had the lowest innate basal intracellular levels of hydrogen peroxide and superoxide among the four different cell types examined. Hence, the observed higher resistance of undifferentiated hESC to oxidative stress and genotoxic stress compared to somatic cell types, as reported by our previous studies [5,6], could be due to lower innate basal intracellular levels of ROS within hESCs compared to somatic cell types. Our findings are consistent with previous studies which showed that ROS play crucial roles as secondary messengers during stem cell differentiation into various somatic lineages [10,11], so that an increase in ROS levels in differentiated stem cell progenies is therefore expected.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…4 According to an MTT test, viability of ESC treated with low doses of hydrogen peroxide was higher than viability of dermal fibroblasts exposed to equal oxidative stress. 5 However, most data suggest that hESC are very prone to apoptosis induced by DNA-damaged agents: etoposide, a topoisomerase II inhibitor, 6,7 UV-exposure 8 (Luo, 2012) and γ-irradiation. 9 Paradoxically, but in spite of hESC high susceptibility to genotoxic agents, DNA repair system in hESC is more efficient relative to non-pluripotent cells.…”
Section: Heat Shock Induces Apoptosis In Human Embryonic Stem Cells Bmentioning
confidence: 99%
“…In a survivability assay (MTT), hESC were more resistant to oxidative stress than fibroblasts that had differentiated from hESC [48]. Survivability was not enhanced for either cell type by heat-shock pretreatment or by preconditioning with low levels of oxidative stress.…”
Section: Examples Of Studies That Have Been Donementioning
confidence: 95%